Discussion: On the Pricing of Preferred Stock - Hoffmeister, J. Ronald (Journal of Financial and Quantitative Analysis, 1981)
Professors Sorensen and Hawkins (hereafter SH) have utilized regression analysis to examine the pricing of preferred stocks both before and after a particular event. This event, the NAIC event, occurred in 1979 when the National Association of Insurance Commissioners (NAIC) adopted a rule permitting insurance companies to carry sinking fund preferred issues at book value rather than at the market value required before. SH results indicate nine to 12 variables have a significant effect on the pricing of preferred stock.